Analisis Tingkat Kerawanan Banjir Lahan Sawah Berbasis Sistem Informasi Geografis di Kecamatan Palas Kabupaten Lampung Selatan - Amin, Muhammad; Ridwan, Ridwan; Asmara, Sandi; Perdana, Tio Arya (abe.fp.unila.ac.id, 2022)
Palas District is one of the districts with the largest rice field area in South Lampung which has 5.589 hectares of rice fields. With such a large rice field area, Palas District in 2020 recorded a rice production figure of around 53,458 tons with a productivity of 58.84 quintals/hectare. This number could increase if there were no rice fields that failed to harvest due to the flood disaster. In 2017 around 345 ha of rice plantations in six villages, Palas sub-district experienced flooding. The flood event was repeated again in 2019, where 200 hectares of paddy fields were flooded. In the latest incident in February 2021, as many as 298 hectares of rice plantations spread across 7 villages, Palas District, experienced a loss due to flooding. In terms of mitigation, mapping of disaster vulnerability and disaster risk can utilize remote sensing and geography information system (GIS) technology. This study uses overlay and scoring methods with six flood variables, namely rainfall, soil type, land use, land slope, land elevation, river density. The mapping carried out will be validated with actual field conditions. The results showed that 77% (3840.45 Ha) of paddy fields were in the